2020
DOI: 10.3390/ma13010161
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Structural Properties of a High-Nb TiAl Alloy Powder

Abstract: TiAl-based alloys are promising light weight structural materials for high temperature applications in the field of aerospace. Recently, fabrication technologies starting from powders including powder metallurgy and additive manufacturing have been developed to overcome the difficulties in the processing, machining and shaping of TiAl-based alloys. Spherical alloy powders with different particle size distributions are usually used in these fabrication techniques. The purpose of this study is to reveal the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Moreover, a cellular dendritic interior microstructure was observed, a characteristic microstructure of rapidly solidified metal droplets. In a related study, Liu and associates [28] studied the size-dependency on structural properties of a Ti-48Al-2Cr-8Nb (at. %) powder alloy produced using EIGA for PM and additive manufacturing technologies.…”
Section: Gas Atomization (Ga)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a cellular dendritic interior microstructure was observed, a characteristic microstructure of rapidly solidified metal droplets. In a related study, Liu and associates [28] studied the size-dependency on structural properties of a Ti-48Al-2Cr-8Nb (at. %) powder alloy produced using EIGA for PM and additive manufacturing technologies.…”
Section: Gas Atomization (Ga)mentioning
confidence: 99%
“…Voluntarily, a process control agent (PCA) is also added to aid in minimising cold welding and lump formation. Collisions between the wall of the Several studies involving the use of GA and SPS have been carried out to date [27][28][29][30]. Gu et al [27] fabricated pre-alloyed (PA) Ti-43Al-5Nb-2V-Y (at.…”
Section: Mechanical Milling (Mm)mentioning
confidence: 99%
“…With the advantages of low density, high melting point, and high specific strength, TiAl alloy has great potential in the field of aerospace. Numerous scholars have carried out studies on the processing methods and mechanical properties of TiAl-based alloys [ 1 , 2 , 3 , 4 ]. Cheng et al [ 5 ] studied the high-temperature deformation properties of a TiAl-based alloy and found that super-plasticity occurs—that is, when the temperature reaches 1000 ℃, the deformation mechanism of this alloy converted from the original dislocation slip and twinning to a grain boundary sliding mode.…”
Section: Introductionmentioning
confidence: 99%
“…TiAl alloys are of great interest in high-temperature applications due to their low density, high specific strength, oxidation resistance, and good structural stability at high temperatures [1,2]. In recent years, research has shifted toward high-Nb TiAl alloys due to their higher service temperatures, which makes them attractive for replacing some Nibased superalloys in applications such as gas turbine engines [3][4][5].…”
Section: Introductionmentioning
confidence: 99%